Pengaruh Suplementasi Besi Terhadap Profil Darah Mahasiswi Akper Dharma Husada Kediri - Erna Susilowati (coba, 2015)
Background: the prevalence of anemia in Indonesia is still high and special countermeasures with appropriate interventions. Iron levels for young women was greatly influenced by the number of consumption food, the part that is absorbed through the gastrointestinal tract, iron deposits in the tissues, excretion and body immunity. The purpose of this research are known the effect of iron supplementation on blood profile in AKPER Dharma Husada Kediri. Methods: this research used experimental research with Randomized Control Trial Design. The subject taken by simple random sampling as much as 40 sample and are divided into 2 groups, Group A in treatment of 20 students give 1 tablet of iron supplementation every day and 20 students group B were given iron supplementation 1tablet each week for 6 weeks. The Data obtained by students taking anemia blood samples and checked his blood in the lab profile Sam Husada Kediri. Nutrient intake from the 24-hour food recall and processed used nutri survey. Data analysis used the paired t test tests for changes in blood profile on each group, independent t test to tell the difference between groups and blood profile test Mann Whitney U test Results: prevalence of anemia in AKPER Dharma Husada of Kediri are 44.3%. Iron supplementation can increased the levels of blood profiles the two groups (p Hb= 0,000, p eritrosit = 0,000, p MCV= 0,000, p MCH = 0,013 dan p MCHC = 0,003) and no significant differences in the levels of blood profiles between the two groups (p Hb= 0,661, p eritrosit = 0,250, p MCV = 0,413, p MCH = 0,76, p MCHC = 0,5935). Conclusion:. Comparison of iron supplementation by students aged 18 – 20 years old no difference in improved blood profiles. Further research needs to be done to clarify the factors that can affect the iron supplementation in the prevention of anemia in AKPER Dharma Husada Kediri. Keywords: Anemia, Iron Supplementation, blood Profiles